The Influence of Green Marketing, Brand Image and Customer Orientation on Purchase Intention of Zorlien Led Products Moderated by Internet Technology - Muhammad Junaid Kamaruddin; Rahmi Darnis (Economic, Management, Business and Accountancy International Journal, 2024)
This research is a direct consumer buying interest in zorlien led products based on green marketing, brand image and customer orientation through internet technology consisting of 250 questionnaire respondents who have been filled in by consumers. The results of 250 respondents consisting of 17 indicators using smartpls were declared valid, because the validity test value above the average> 0.5 and the reliability test above the average> 0.7. The results of the brand image hypothesis test, green marketing, customer orientation and internet technology on purchase intention are significant, but when coded the results are not significant